ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN DAN KELAYAKAN USAHA AGROWISATA STRAWBERRY (Fragaria choiloensis L.) PETIK SENDIRI (Studi Kasus : Kabupaten Karo) - Muhammad JufriansyahMuhammad Jufriansyah; Gustami Harahap; Mitra Musika Lubis (Universitas Medan Area, 2019)
In North Sumatra there is one type of horticulture plant, strawberry, especially in Karo district. The purpose of this study was to find out what factors influence the level of income of strawberry picking agrotourism farmers themselves, knowing the price of their own picking strawberry agro-tourism business and knowing whether the picking strawberry agro- tourism business itself is feasible. The sampling method is used by the Central theorem limit method, the total population of strawberry farmers in Karo Regency is 60, in this study 30 farmers were made as representative samples of the entire population. The data collected is primary and secondary data. The analytical method used is multiple linear regression with SPSS 21, BEP software tools and business feasibility analysis using R / C Ratio. (1) From the study using multiple linear regression analysis tools which have positive effect on strawberry farmers' income, namely sales and expenditure volume of RT. (2) Analysis of data from (BEP), it is known that the sales volume reaches the level of 478.80 Kg with a selling price of Rp. 52,760 / Kg, then the sales result is Rp. 38,304,239, with the results of the sale, the strawberry picking agro-business itself was declared even. (3) Analysis of the feasibility of the own strawberry picking agrotourism business in Karo Regency, obtained the results of R / C> 1, then the business is economically feasible.